AFONSO DA MAIA, DA LITERATURA À TELEVISÃO: O processo de transposição do patriarca Maia do romance eciano para a minissérie global - Vogler, Bianca do Rocio (2014)
In this dissertation, I analyze how the character Afonso da Maia is built in the novel The Maias, by Eca de Queiroz, and in the eponymous miniseries, originally broadcast in Brazil by Globo TV in 2001, having the playwright Maria Adelaide Amaral as a screenwriter, Luiz Fernando Carvalho as a director and the actor Walmor Chagas as a performer of this character. Thus, initially, the observation of some characteristics of Eça's writing enables us to understand the way the Portuguese writer uses them in the process of creating the character of the patriarch Maia in order to compose both the physical and psychological makeup of what I consider to be the fundamental character in the novel. And as the analysis is guided by the relationship between the television adaptation and the literary text on which it is based, I see that the theoretical concepts to be covered must contribute to the understanding of the dialogism that presents itself as basic to every creative movement. Thus, by taking into account certain concepts of the theories of Walter Benjamin and Mikhail Bakhtin, I mean to provide an understanding of how the approaches of the two philosophers, each in his own area and developing his views about different issues, may contribute to the study of the relationship between literature and film/television, especially regarding the audiovisual adaptations of literary texts. And, from such considerations with respect to how the character Afonso da Maia is built through some of the specifics of Eça de Queiroz's writing and also the issues detected in the relationship between the literary and the audiovisual media, I seek to investigate how the authors of the television text perform the adaptation of such character to a medium with distinct features of significance, but nonetheless manage to appropriate certain elements used by the Portuguese writer, as well as undertake some additions and modifications, in order to build the senses that pertain to the figure of the patriarch.